Analysis of the sexual dimorphism of metric variables of the cranial base: Archaeo-anthropological and forensic implications - Alexandra Boucherie (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
Estimating biological sex is a fundamental step in assessing the biological profile of human remains, whether recovered from archaeo-anthropological or forensic contexts. As the methods based on the os coxae are not systematically applicable, alternative means of sexual diagnosis are needed. This morphometric study examines the sexual dimorphism of the cranial base (i.e., occipital, temporal bones and bony labyrinth) using a corpus of 611 skulls and 121 bony labyrinths from identified individuals – both immature and adult – from Western Europe. The study shows how the expression of this sexual dimorphism becomes more marked on the temporal bone as from the pubertal growth peak. Thirteen predictive models, with a classification accuracy ranging from 77 to 87% with a 0.70 decision threshold, were developed based on the adult cranial base. The models were also applied, successfully, to 3D cranial surfaces. Our study demonstrates that an age-independent sex estimation method cannot be designed on the bony labyrinth. Taking into account the specific features of immature and adult sexual dimorphism, predictive models were built up that yielded, respectively, up to 76-83% and 73-86% accuracy. This research thus offers a new method of sexual diagnosis which is better suited to fragmentary adult remains, and thereby contributes to the discussion about the need to set up a standardized analytical framework for future developments in sexing methods.